Effectiveness of Women’s Self-care Instructions concerning Wound, Perineal & Urinary System Care post cesarean section in Baghdad teaching hospital - Kadhim, amel; ali, Rabea (Iraqi National Journal of Nursing Specialties, 2018)
Aim: to determine the effectiveness of women’s self-care instructions on their post cesarean section care in Baghdad teaching hospital. Methodology: The present study used quasi-experimental study design in maternity words in Baghdad teaching hospital. The sample was collected and follow up for the period (15) January 2014 until 15 May 2014 Nonprobability (purposive sample) of (100) women post cesarean section divided in to two groups (50) women post cesarean section considered as a study group, and another (50) women post cesarean section considered as the control one, A questionnaire designed as a tool to collect data fit the purpose of the study a questionnaire include demographic variables, Reproductive variables, instructions self-care post cesarean Wound care, a pilot study was carried out to test the reliability, As for reliability of questionnaire has been displayed by a group of experts in various medical specialties and nursing .Result: The study presents significant differences in implementation of instructional program for self-care post cesarean between study and control groups on wound, there is significant differences in washing hand before & after any procedure, Don’t put ointment or cream on the wound, don’t raise the dressing to see operation immediately unless done by medical staff (P=0.000). Also significant differences are found in perineal care & urinary system post cesarean in washing hand before & after using bathroom, wash perineum area water warm water contains a antiseptics from front of the pubic bone to the anus, place sanitary pads from front to back to protect the inner surface from contamination, do not hold on the urine when feel the desire to urinate, practice kegel exercises 2-3 times per day, Do not have sexual intercourse during the first 6 weeks, preferred to use the western bathroom (P= 0.000). Recommendations: The study recommended the possibility of providing an educational overlap of self-care after a cesarean delivery for all pregnant women attending antenatal care centers, primary health, construction and application of the overlap of the mothers of the educational process to be holding them in the hospital to increase their knowledge of self-care after a cesarean section